Whole-Brain Atrophy Differences between Progressive Supranuclear Palsy and Idiopathic Parkinson’s Disease - Guevara, Carlos; Bulatova, Katherina; Barker, Gareth J.; Gonzalez, Guido; Crossley, Nicolas A.; Kempton, Matthew J. (Frontiers in Aging Neuroscience, 2016)
Background: The absence of markers for ante-mortem diagnosis of progressive supranuclear palsy (PSP) results in this disorder’s being commonly mistaken for other conditions, such as idiopathic Parkinson's disease (IPD). Such mistakes occur particularly in the initial stages, when ‘plus syndrome’ has not yet clinically emerged. Objective. To investigate global brain volume and tissue loss in patients with PSP relative to patients with IPD and healthy controls and correlations between clinical parameters and magnetic resonance imaging (MRI)-derived brain volume estimates. Methods: T1-weighted images were obtained from three groups of Chilean Latin American adults: 21 patients with IPD, 18 patients with PSP and 14 healthy controls. We used Structural Imaging Evaluation with Normalization of Atrophy (SIENAX) to assess white matter, gray matter and whole-brain volumes (normalized to cranial volume). Imaging data were used to analyze putative correlations with the clinical status of PSP and IPD patients using the Unified Parkinson’s Disease Rating Scale Part III, Hoehn and Yahr, the Clinical Global Impression for Disease Severity Scale and the Frontal Assessment Battery. Results: PSP patients had significantly lower whole brain volume than both IPD patients and controls. Whole brain volume reduction in PSP patients was primarily attributable to gray matter volume reduction. We found a significant correlation between brain volume reduction and clinical status in the PSP group. Conclusions: At the group level, whole brain and gray matter volumes differentiated patients with PSP from patients with IPD. There was also significant clinical-imaging correlations with motor disturbances in PSP.